Model Peningkatan Loyalitas Nasabah Internet Banking Berbasis Persepsi Resiko, Persepsi Privasi dimediasi Kepercayaan dan Kepuasan Nasabah - Muhammad Ras Muis; Muhammad Fahmi; Muhammad Andi Prayogi; Jufrizen Jufrizen (University of Merdeka Malang, 2021)
This study aims to examine the factors that influence internet banking customer loyalty in Medan City. The location of this research was carried out at several banks in the city of Medan. The population in this study were all bank customers who use internet banking and the total sample was 175 customers. Researchers used the Structural Equation Modeling assisted by the Lisrel 8.80 program in this research. The results showed that risk perceptions have a negatif and significant effect on customer satisfaction and customer trust. Perception of Privacy has a positive and significant effect on Customer Satisfaction and Customer Trust. Satisfaction has a positive and significant impact on Customer Trust. Perception of risk has a negatif and significant effect on customer loyalty. Perception of Privacy has a positive and insignificant effect on Customer Loyalty. Satisfaction has a positive and significant effect on Customer Loyalty and Trust Has a positive and significant effect on Customer Loyalty. Satisfaction and trust can negatifly mediate the effect of Risk Perception on Customer Loyalty. Satisfaction and trust can positively mediate the effect of Perceptions of Privacy on Customer Loyalty. Trust Satisfaction can positively mediate the effect of satisfaction on Customer Loyalty